ASPEK MORALITAS NOVEL RANTAU 1 MUARA KARYA AHMAD FUADI RELEVANSI BAHAN AJAR SASTRA - Santika, Desintia Mutiara; Saputri, Hidayah Nurul; Sudiatmi, Titik (Jurnal Bahasa Indonesia Prima (BIP), 2023)
The research used a qualitative descriptive method; the descriptive presentation was carried out according to facts and phenomena, not in the form of numbers or writing variables with the title "Aspects of Morality of the Rantau 1 Muara Novel by Ahmad Fuadi" aimed at reviewing the point of view contained in the novel Rantau 1 Muara by Ahmad Fuadi. The results of this research analysis using structural theory are as follows: the morality aspect in the Rantau 1 Muara novel includes the human relationship with God, oneself, and other humans, as well as relevance as learning material in high school. This article is able to increase knowledge of literature in relation to society. The aspect of literary morality aims to organize one's personality through moral values ​​taught in moral studies in the world of education so as not to do things that can damage one's morals so that one becomes a good person.